Apple (Malus domestica) phenolic compounds in the prevention of oxidative stress in physical activity: literature review (Research, Society and Development, 2021)
The practice of physical activity is the way to bring quality of life to the population, and currently society is increasingly concerned and aware of the benefits it brings to mental and physical health, thus avoiding various diseases because the body needs to be in motion. However, some studies report that physical activity, both aerobic and anaerobic, when it exceeds the cell's capacity of reversibility to return to its original situation, brings consequences to muscles such as oxidative stress. Some studies have reported that the consumption of phenolic compounds has avoided high muscle stress and this is because they are able to reduce the oxidation of organic compounds during physical activities produced during cellular respiration. The objective of this review is to demonstrate why apple (Malus domestica) consumption before aerobic and anaerobic training avoids oxidative stress. After a literature review in articles, books and search sites related to the topic, it was concluded that apples are rich in phenolic compounds, and that a portion of 140 g/ml of apple has 406.11 mg of polyphenols, being the most suitable fruit. for use in food in order to avoid muscular oxidative stress compared to kiwi fruit and other fruits as presented in this work and that the daily consumption of 1000 mg of polyphenols is necessary for the prevention of oxidative stress.